PENDAMPINGAN PENGUATAN LITERASI DIGITAL MELALUI PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BAGI GURU PAI SMA DI PAMEKASAN - Fathorrozy, Fathorrozy; Nurhayati, Sri; Hasan, Nor; Maghfiroh, Muliatul; Suwantoro; Yaqin, Ainul; Mannan, Abd.; Kutsiyyah; Sa’i, Mad (CV. Jendela Gagasan, 2025)
This community service article aims to examine the implementation of Assistance in Strengthening Digital Literacy through Training on the Development of Learning Media for Islamic Education (PAI) Teachers at Senior High Schools in Pamekasan. The method used in this program is the PIJAR model, which consists of four stages: planning, organizing, implementation, and evaluation. The results of the training show that the implementation of the community service program with the theme